Pewien Przypadek Ściskania Mimośrodkowego w Ujęciu Nieliniowym - Szuwalski, K. (Engineering Transactions, 1970)
In this paper is considered the frequently found case of eccentric compression – loading of a bar unilaterally fixed by the weight of a certain body resting on its free end. The point of application of the compressing force is then above the free cross-section at height a (equal to the distance of the centre of gravity of the body from the free end of the bar). The influence of the segment a upon the bending of the bar are determined on the basis of the exact nonlinear equation of the bending line, consideration being given to the influence of the rotation of the free and of the bar. The result has been obtained in the form of an incomplete elliptical integral of the first kind. Subsequently, parametrization of the solutions numerical calculations are made, the results of which are presented graphically. The case of the limiting transition to axial compression is considered, and the approach of the ends of the bar is calculated.